Changes in the functionality of tear film and autorefractometry reading after instillations of artificial tear products of different viscosity - V.V. Brzheskiy; E.L. Efimova; M.A. Kopylova; P.V. Kocharina; A.A. Primak; V.P. Nikolaenko (РМЖ "Клиническая офтальмология")
V.V. Brzheskiy1, E.L. Efimova1, M.A. Kopylova1, P.V. Kocharina1, A.A. Primak1, V.P. Nikolaenko2 1St. Petersburg State Pediatric Medical University, Saint-Petersburg, Russian Federation 2St. Petersburg State University, Saint-Petersburg, Russian Federation Aim: to study the changes in the critical parameters of tear film stability and autorefractometry in patients with mild dry eye syndrome (DES) after instilling artificial tear products of different viscosity. Patients and Methods: thirty patients aged 23–70 with mild bilateral DES were examined using the Visionix VX120+Dry Eye multi-diagnostic unit equipped with the TF-Scan to fix and assess tear film stability and tear breakup time (TBUT). The critical refraction and tear film parameters were evaluated by keratometry, corneal topography, TBUT, and tear meniscus height measurements. Next, an artificial tear product was instilled, i.e., group 1 (14 patients, 28 eyes) received a 0.15% sodium hyaluronate-based preparation, and group 2 (16 patients, 32 eyes) received a 0.4% sodium hyaluronate-based preparation. The examination was repeated after 30 sec and 5 min. Controls were seven healthy individuals (14 eyes). Results: in DES, breaks in the tear film appeared earlier and affected greater corneal surface area. A "Destabilized tear film area" parameter of the Visionix VX120+Dry Eye contributed significantly to the knowledge of tear film functionality, thereby empowering the diagnostic armamentarium in DES. As early as 30 sec after instillation of both artificial tear preparations, breakup-free time tended to increase, while the area of tear film destabilization tended to reduce. After 5 min, this trend continued to increase, particularly after instilling 0.15% sodium hyaluronate-based preparation. At the same time, changes in keratometry readings (i.e., sphere and cylinder) and astigmatism axis orientation were reported. Corneal refractive power (more in the flattest axis) increased, in particular, after the instillations of 0.15% hyaluronic acid. The range of changes was 0.00–0.75 D for the sphere power, 0.00–0.50 D for the cylinder power, and 0–69 degrees f or astigmatism axis orientation. Conclusions: our findings with the Visionix VX120+Dry Eye multi-diagnostic unit demonstrate a significant variation of autorefractometry readings in DES depending on the extent of ocular surface hydration. These phenomena raise questions about the accuracy of autorefractometry readings. Therefore, autorefractometry should be performed after normalizing tear film volume and stability. Keywords: dry eye syndrome, Visionix®, autorefractometry, tearscopy, the effect of artificial tears on results. For citation: Brzheskiy V.V., Efimova E.L., Kopylova M.A. et al. Changes in the functionality of tear film and autorefractometry reading after instillations of artificial tear products of different viscosity. Russian Journal of Clinical Ophthalmology. 2021;21(4):200–204 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-200-204.